Vaginal Colonization by papG Allele II+ Escherichia coli Isolates from Pregnant and Nonpregnant Women as Predisposing Factor to Pyelonephritis - Sareaa Maseer Gatya Al-Mayahie (Hindawi Limited, 2013)
Vaginal (61) and fecal (61) Escherichia coli isolates from pregnant and nonpregnant women (18-45 years old) were surveyed for papG alleles by PCR technique. papG allele II was the most prevalent among both vaginal (32.7%) and fecal (3.2%) isolates, whereas other alleles were found only among vaginal isolates (1.6% for alleles I and III and 3.2% for alleles II + III). papG+ pregnant women's isolates did not differ significantly from those of nonpregnant in possession of papG allele II (90% versus 73.3%), whereas both (32.7%) differed significantly (P≤0.05) in comparison with fecal isolates (3.2%). The vast majority of papG allele II+ vaginal isolates were clustered in group B2 (81.8%) and much less in group D (18.1%). Also, most of them were positive for fimH (100%), papC (100%), iucC (90.9%), and hly (72.7%), and about half of them were positive for sfa/foc (45.4%). In addition, the mean of VFs' gene possession was 3.5 (range from 2 to 5). It can be concluded that vaginal colonization by papG allele II+ E. coli is possibly one of the predisposing factors of both pregnant and nonpregnant women to pyelonephritis, but its potential may be modified by other factors especially host factors.